Managing Contextual Indonesian Language Learning: A Comparative Study of Urban and Rural Elementary Schools - Siti Nurfitriyana; Yosal Iriantara (ITScience (Information Technology and Science), 2026)
This study aims to analyze Indonesian language learning strategies based on the Contextual Teaching and Learning (CTL) model in improving elementary school students’ learning outcomes. The research employed a qualitative approach using a multisite case study design, conducted at SDN Cibeureum Hilir CBM in Sukabumi City and SDN Sungapan in Sukabumi Regency. Data were collected through observations, in-depth interviews, documentation, and learning outcome tests involving teachers, students, and school principals. Data analysis was carried out using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that CTL-based learning strategies are implemented through four main stages: planning, organizing, actuating, and controlling. In the planning stage, teachers design contextual learning activities aligned with students’ real-life experiences, although with varying levels of structure. In the organizing stage, classroom management and collaboration support student-centered learning, despite differences in resource availability. In the implementation stage, CTL creates an active and meaningful learning environment that enhances students’ engagement and language skills. In the controlling stage, evaluation and follow-up actions are carried out through tests, assignments, and observations, although the consistency of these practices varies across schools. The study concludes that CTL-based learning strategies positively improve students’ motivation, participation, and learning outcomes in Indonesian language subjects. However, the effectiveness of CTL is influenced by teacher competence, the availability of learning resources, and the school context. Therefore, strengthening teacher capacity and improving learning facilities are essential to optimize the implementation of contextual learning in elementary education.